Altered levels of amyloid precursor protein intracellular domain-interacting proteins in Alzheimer disease - Chakrabarti, Arunabha; Chatterjee, Atri; Sengupta, Mohor B; Chattopadhyay, Partha; Mukhopadhyay, Debashis (Alzheimer disease and associated disorders, 2014)
The amyloid precursor protein intracellular domain (AICD) is an intrinsically unstructured molecule with functional promiscuity that plays an important role in determining the fate of the neurons during its degeneration. Its association with Alzheimer disease (AD) recently played a key role in propelling scientists to choose AICD as a major molecule of interest. Although several studies have been conducted elucidating AICD's participation in inducing neurodegenerative outcomes in AD condition, much remains to be deciphered regarding the linkage of AICD with cellular pathways in the AD scenario. In the present study, we have pulled down interactors of nonphosphorylated AICD from the cerebrospinal fluid of AD subjects, identified them by matrix assisted laser desorption ionization mass spectrometry, and subsequently studied the differential expression of these interactors in AD and control cases by 2-dimensional difference gel electrophoresis. The study has yielded some AICD-interactors that are differentially expressed in the AD cases and are involved in diverse cellular functions. This proteomic-based approach highlights the first step in finding the possible cellular pathways engaged in AD pathophysiology on the basis of interaction of one or more of their members with AICD.